2015
DOI: 10.21608/bvmj.2015.32511
|View full text |Cite
|
Sign up to set email alerts
|

A survey on presence of new strains of infectious bronchitis virus in some chicken farms of Egyptian Delta provinces during 2014

Abstract: for drawing the epidemiological chart of distribution of IBV through the forementioned localities.The cardinal signs of the disease in layers were drop in egg production, with watery albumen, inferior (pale-misshape shell) eggs, while in broilers were respiratory distress, renal urate deposition and mortality. Identification of IBV was by reverse transcriptase -polymerase chain reaction (RT-PCR) of RNA extracted from trachea and kidney tissues from freshly dead birds. There were 7/16 (about 43.7%) of selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Infectious Bronchitis Virus is a positivesense, single stranded RNA virus. Different genotypes of IBV have been identified allover the world [1,2]. Although the routine and continuous vaccination of chicken with IBV, outbreaks still frequently occur in the field due to the emergence of different variant serotypes beside the classical subtypes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Infectious Bronchitis Virus is a positivesense, single stranded RNA virus. Different genotypes of IBV have been identified allover the world [1,2]. Although the routine and continuous vaccination of chicken with IBV, outbreaks still frequently occur in the field due to the emergence of different variant serotypes beside the classical subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, different researchers concluded that HI test is an IBV serotype specific test, and NT is the gold standard test for the detection of IBV serotype specific antibodies in sera of chickens after single vaccination [1,2,11,[21][22][23]. The specificity of the HI test is considered to be lower than that of the NT.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…IBV strains were previously isolated from different localities by Reda et al (2015), (Chicken / Egypt KP279995 / VACSERA / 2014) (classical ) and (Chicken / Egypt KP279998 / VACSERA / 2014) (variant) The two strains were propagated in SPF-ECE and tittered with infectivity titer 10 8.5 EID 50 / dose as viral seed for preparation of bivalent inactivated IB vaccine and challenge dose was adjusted to be 10 4.5 EID 50 /ml, the titration was calculated according to Reed and muench, (1938).…”
Section: Ibv Strainsmentioning
confidence: 99%